Growth and Risk - Elbers, Chris; Gunning, Jan Willem; Kinsey, Bill (World Bank, 2012)
How exposure to risk affects economic growth is a key issue in development. This article quantifies both the ex ante and ex post effects of risk using long-running panel data for rural households in Zimbabwe. It proposes a simulation-based econometric methodology to estimate the structural form of a micro model of household investment decisions under risk. The key finding is that risk substantially reduces growth in this particular setting: the mean capital stock in the sample is (in expectation) 46 percent lower than in the absence of risk. About two-thirds of the impact of risk is due to the ex ante effect (that is, the behavioral response to risk), which is usually not taken into account in policy design. These results suggest that policy interventions that reduce exposure to shocks or that help households manage risk could be much more effective than is commonly thought.